Leadership Strategy of School Principal in Efforts to Realize Teacher Performance in The Implementation of Independent Curriculum (A Case Study in Hang Tuah 6 Excellent Juanda Middle School) - Raudatul Ula; Warih Handayaningrum; Muhammad Sholeh; Mochamad Nursalim; Amrozi Khamidi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The school principal leadership is very necessary in developing strategies to ensure school quality by making efforts to realize teacher performance, especially in driving schools that have implemented independent curriculum. This research aims to examine the leadership strategies implemented by a principal in an effort to realize teacher performance in implementing the Independent Curriculum; analyze the teacher performance in implementing the independent curriculum; and describe the implementation of the independent curriculum. This research used a qualitative approach with a case study type of research and was conducted in Hang Tuah 6 Excellent Juanda Middle School. The data collection techniques used are in-depth interviews, observation, and documentation. The data analysis techniques used in this research are carried out simultaneously, consisting of data collection, condensation, presentation, and verification/drawing conclusions. The research results show that the principal in implementing the strategy has fulfilled the criteria of strategy implementation by making a systematic and documented strategic plan at the beginning so that its implementation can be measured; monitoring the implementation of the strategy by being open-minded, involving teachers actively and intensively in any school programs, motivating teachers; and always carrying out evaluations as the basis for making improvements.